Effect of Triage Algorithm on Knowledge and Practices Among Nurses in a Teaching Hospital - R. Ponchitra; Kavitha Reddimalla; J. Ferganzia (Innovational: Journal of Nursing and Healthcare, 2025)
Introduction: Triage system in emergency department helps the healthcare workers to make accurate decisions at the right time. In casualty identifying and providing care in a short duration on an urgent basis without consuming time is a priority. Triaging helps in recognizing the severity of illness of the patient. Efficient triage system helps to save the patient in an emergency at the right time. Health professionals can work efficiently if the organization has an established triaging system. The study aims to assess the knowledge and practice on triage management among nurses before and after introducing the triage algorithm. Materials and Methods: Quasi-experimental one group pre-test post-test design was adopted. Data were collected from 60 staff nurses using structured questionnaires on triage management and an observation-based checklist for triage simulation for nurses by the non-probability convenience sampling technique. Results: There is a statistically significant difference between the mean score of knowledge in pre-test score and post-test score at 5% level of significance as P < 0.05. There is a statistically significant difference between the mean score of practice in pre-test score and post-test score at 5% level of Significance as P < 0.05 highly significant at 0.01% level, that is, P < 0.001. Conclusion: In the present study, it is found that the triage algorithm is strongly associated with the outcome of the nurses by recognizing the priority of the patient. It is found that triage algorithm flow chart is helpful to recognize according to the color code in a mass casualty situation.